Dynamic Alternative Splicing During Mouse Preimplantation Embryo Development - Xing, Yongqiang; Yang, Wuritu; Liu, Guoqing; Cui, Xiangjun; Meng, Hu; Zhao, Hongyu; Zhao, Xiujuan; Li, Jun; Liu, Zhe; Zhang, Michael Q.; Cai, Lu (Frontiers in Bioengineering and Biotechnology, 2020)
The mechanism of alternative pre-mRNA splicing(AS) during preimplantation development is largely unknown. In order to capture the dynamic changes of AS occurring during embryogenesis, we carried out bioinformatics analysis based on scRNA-seq data over the time-course preimplantation development in mouse. We detected numerous previously-unreported differentially expressed genes at specific developmental stages and investigated the nature of AS at both minor and major zygotic genome activation(ZGA). The AS and differential AS atlas over preimplantation development were established. The differentially alternatively spliced genes(DASGs) are likely to be key splicing factors(SFs) during preimplantation development. We also demonstrated that there is a regulatory cascade of AS events in which some key SFs are regulated by differentially AS of their own gene transcripts. Moreover, 212 isoform switches(ISs) during preimplantation development were detected, which may be critical for decoding the mechanism of early embryogenesis. Importantly, we uncovered that zygotic AS activation(ZASA) is in conformity with ZGAand revealed that AS is coupled with transcription during preimplantation development. Our results may provide a deeper insight into the regulation of early embryogenesis.